PERANCANGAN SISTEM PAKAR MENDETEKSI KERUSAKAN NOTEBOOK MENGGUNAKAN METODE FORWARD CHAINING - Prasetyo, Aditya; Ferga Prasetyo, Tri (Universitas Majalengka, 2019)
Health is very important for humans , including infants . Largely due to the mild symptoms such as fever and flu. In general, people quite understand how to deal with the symptoms of mild disease in children. But it would be better to include the medical role in detecting the symptoms of a disease fatal to children. So that needs to be made an application based on medical knowledge to diagnose the disease in children who are used as a tool to obtain information about the child's illness and give advice as the first action should be taken to tackle the disease in children. Knowledge base into a highly structured database with multiple tables.Inferences in this expert system uses forward chaining inference method. Expert system will provide questions to the user in the form of the symptoms of some disease and the user will answare that question. Until the user will get the solution of the question. The author makes this application with PHP programming languages and database using MySQL.